Numerical simulation of a shock tube in thermochemical non-equilibrium - Clarke, JP; Glenn, A; McGilvray, M; Di Mare, L (American Institute of Aeronautics and Astronautics, 2023)
An efficient method is developed for calculating the non-equilibrium properties of the test gas in a shock tube in the shock frame of reference. The one dimensional method is based on the parabolised Navier-Stokes equations, resulting in a form similar to a stagnation line problem but with appropriate consideration of the mass loss to the boundary layer present in a shock tube. Gas properties are determined using Park’s two temperature model. Transport properties are evaluated using second order Chapman-Enskog theory. The centreline solution is coupled to an artificial radial pressure profile which mimics the effect of a boundary layer. The method was tested on a variety of air cases ranging from 5.5 km/s to 9.6km/s, and demonstrated improved modelling of the non-equilibrium regions compared to a Rankine-Hugoniot solver. A 6.1 km/s, 13.3 Pa test case relevant for Titan entry demonstrates the necessity of appropriately modelling mass loss to the boundary layer in a shock tube. The effect of shock structure and mass loss to the boundary layer in a non-equilibrium flow within a shock tunnel is shown to substantially impact the test gas properties and non-equilibrium radiance profiles in the UV/Vis and Vis/IR regions.